Impact of rural infrastructure on performance of livestock sector in Uttar Pradesh - KUMAR, SHIV; KUMAR, SANJEEV; JOSHI, DEVNA; UPADHYAY, SANJAY KUMAR; SINGH, DHARAMRAJ (The Indian Journal of Animal Sciences, 2020)
This paper examines the emerging trends and growth of livestock sector at disaggregate level in Uttar Pradesh (UP) from 2004–05 to 2015–16. The share of crop sector in GSDP had declined sharply while livestock sector gained a significant share due to consistent higher growth in agricultural sector of the state. The regional level result indicated that Western UP outperformed Eastern, Central and Bundelkhand regions in that order with high disparities across the regions in case of livestock sector as well as rural infrastructure. Moreover, Fixed Effects model attested a positive and significant relationship between value of output by livestock and rural infrastructure index. It suggested that adequate development avenues via rural infrastructure, extension services, value chain development and research investments can boost the growth of livestock sector and mainstreaming the livestock development. Also, the state can utilize the opportunities by promoting livestock as a dominant approach towards livelihood diversification as adopted by other states as well. This will not only take care of the already overstressed agriculture sector but will also be instrumental in attaining the objective of doubling farmers’ income.